Chemical and biological properties of a peptidoglycan isolated from Treponema pallidum kazan. - Umemoto, T (1981)
A peptidoglycan layer of Treponema pallidum kazan was isolated by solubilization of whole cells with 1% warm sodium dodecyl sulfate and subsequent digestion of an insoluble residue with proteases. Electron microscopy revealed that the peptidoglycan was isolated as a single-layered sacculus of less than 5 nm in thickness, freed from axial filaments and an envelope sheath. An isolated peptidoglycan fraction was mainly composed of glucosamine, muramic acid, alanine, glutamic acid, ornithine, and glycine in molar ratios of 0.65:0.68:1.63:1.00:0.75:1.03. Amino (N)- and carboxyl (C)-terminal amino acid analyses suggested the involvement of at least a part of the glycine residue in cross-linking between the amino group of ornithine residue at one strand of the stem peptide subunit and the carboxyl group of alanine of the neighboring strand. The treponemal peptidoglycan lacked the immunoadjuvant activity both to stimulate antibody production and to induce delayed-type hypersensitivity against ovalbumin, as well as the properties necessary to stimulate guinea pig and mouse splenocytes and guinea pigs peritoneal macrophages, unlike the cell walls or peptidoglycans (group A type of Schleifer and Kandler's classification, Bacteriol. Rev. 36:407-477, 1972) isolated from many bacterial species parasitic to the mammal. However, the peptidoglycan activated the human complement system through the alternative pathway, as well as the classical one, and caused a liberation of 5-hydroxytryptamine in rabbit blood platelets in a similar manner to the cell wall peptidoglycans of both group A and B types.